Natural Science Big Book with Baduy Local Wisdom Base Media Development for Elementary School (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2017)
Big Book is an especially characterized storybook that being enlarged, both the text and the pictures and designed as interesting as possible so it could motivate the students in learning the lesson in school. Big Book media in this research was developed based on local wisdom in Baduy as the effort to introduce the local wisdom values in Baduy custom area, so it may grow the love towards the local custom. The benefit of using the local wisdom based Big Book is the teacher can easily interest the students to focus on the story that will be read and make it easier for the students in understanding the material because the contents of the material are related directly to the student’s daily life. From the data that have been gathered, there are 79.7% to learning material expert validation and 83.41% to learning media validation. So, it can be concluded that Big Book media is appropriate to be used in the learning process.